From the Trees to the Wood: Alternative Spirituality as an Emergent ‘Official Religion’? - Kapusta, Jan (Journal of religion in Europe, 2020)
Abstract In this introductory study, we place the articles collected in this special issue on ‘spirituality’ in a more general context. In so doing, we contest the idea that alternative spirituality is best studied within the conceptual framework of the ‘vernacular.’ We argue that such an approach tends to unintentionally overstate the empirical particularities and overlook the broader aspects of the subject in question, which results in unreflexively accepting alternative spirituality’s own claim that it is ‘doctrine-free’ and ‘non-institutional’ by nature. Contrary to this claim, we show that alternative spirituality is (a) pregnant with a distinguishable doctrine despite being glocal and inventive; (b) profoundly social and effectively socialized; (c) about to be visibly socially organized and institutionalized; and (d) a way of addressing and redressing the key existential issues of human life, just as any other religion.